Production of spirulina platensis using dry chicken manure supplemented with urea and sodium bicarbonate - Thepparath Ungsethaphand (2018)
The cyanobacterium Spirulina platensis is an attractive source of valuable protein for both human and animal consumption. The conventional nitrogen source for S. platensis is nitrate. However, recent research has evaluated the potential of using animal waste as a low-cost nitrogen source. In this work, the cultivation of S. platensis was done using dry chicken manure (DCM), collected from a closed-system poultry house, as nitrogen source. The experiment was carried out in open concrete tanks with 100 litres of culture medium and an initial biomass concentration of 0.5 g/L. The culture media were prepared to test the effect of unsupplemented DCM, DCM supplemented with 2.0 mg/L of urea (DCM+U), and/or 40 mg/L of sodium bicarbonate (DCM+U+B or DCM+B). The best cellular growth and highest protein production were observed for S. platensis in the biomass harvested from the culture medium containing DCM supplemented with 2.0 mg/L of urea (DCM+U). © 2009 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.